Nilotinib in patients with systemic mastocytosis: analysis of the phase 2, open-label, single-arm nilotinib registration study - Hochhaus, Andreas; Müller, Martin Christian; Reiter, Andreas (Journal of cancer research and clinical oncology, 2015)
PurposeActivating KIT mutations are part of the pathogenesis of systemic mastocytosis (SM). Nilotinib is a tyrosine kinase inhibitor that potently inhibits activated forms of KIT. This phase 2, open-label, single-arm study (CAMN107A2101; www.clinicaltrials.gov NCT00109707) evaluated nilotinib in patients with SM.MethodsPatients with SM [aggressive SM (ASM), indolent SM, or other] received nilotinib 400 mg twice daily. C-findings were collected retrospectively to assess response using criteria proposed after trial initiation. Response was evaluated using improvements in laboratory findings (for all patients) and ASM response criteria (for the ASM subgroup).ResultsIn 61 patients enrolled, the median nilotinib exposure was 232 days (range 3-1274 days) with a median follow-up of 34.7 months. In patients with ASM (n = 37), the overall response rate was 21.6 %. In the eight responders, all of whom had a KIT D816V mutation at any time, mast cell infiltration and tryptase level decreased by 70 % and 29.8 %, respectively; absolute neutrophil count increased by 94.7 %. Laboratory parameters also improved in the non-ASM subgroups. Overall survival at 24 months was 81.2 % (95 % CI 70.6-91.8 %) with median survival not yet reached. New or worsening grade 3/4 hematologic adverse events (AEs) included thrombocytopenia (10.3 %), anemia (10.0 %), and neutropenia (6.9 %). The most common grade 3/4 nonhematologic drug-related AEs were diarrhea (6.6 %) and headache (4.9 %). Eleven patients (9 with ASM, 2 with MCL) died, 10 due to progressive disease; 7 deaths occurred ≥28 days after treatment discontinuation.ConclusionsNilotinib 400 mg twice daily was effective in some patients with SM, including patients with mutated KIT D816V.